Evaluation of an Ultrasound-Based Navigation System for Spine Neurosurgery: A Porcine Cadaver Study - Gueziri, Houssem-Eddine; Rabau, Oded; Santaguida, Carlo; Collins, D. Louis (Frontiers in Oncology, 2021)
Background: With the growing incidence of patients receiving surgical treatment for spinal metastatic tumours, there is a need for developing cost-efficient and radiation-free alternatives for spinal interventions. In this paper, we evaluate the capabilities and limitations of an image-guided neurosurgery (IGNS) system that uses intraoperative ultrasound (iUS) imaging for guidance. Methods: Using aA lumbosacral section of a porcine cadaver, was used in this study. Wewe explored the impact of CT image resolution, ultrasound depth and ultrasound frequency on the system accuracy, robustness and effectiveness. Preoperative CT images with an isotropic resolution of 0.5mm^3, 1mm^3 and 2mm^3 were acquired. During surgery, vertebrae L1 to L6 were exposed. For each vertebra, five iUS scans were acquired using two depth parameters (5 cm and 7 cm) and two frequencies (6 MHz and 12 MHz). A total of 120 acquisition trials were evaluated. The Ultrasound-based regisration performance is compared to the standard alignment procedure using intraoperative CT. We report the target registration error (TRE) and the computation time. In addition, the scans' trajectories were analyzed to identify vertebral regions that provide the most relevant features for the alignment. Results: For all acquisitions, the median TRE ranged from 1.42 mm to 1.58 mm and the overall computation time was 9.04 s ± 1.58 s. Fourteen out of 120 iUS acquisitions (11.66 %) yielded a level-to-level mismatch . No significant effect on accuracy was found between the accuracy and thewith CT resolution (F_((2,10))=1.70,p=0.232),. There is no significant effect of depth (F_((1,5))=0.22,p=0.659) nor frequency (F_((1,5))=1.02,p=0.359) on the accuracy. The While misalignment increases linearly with the distance from the imaged vertebra, and the accuracy was satisfactory for directly adjacent levels. A significant relationship was found between iUS scan coverage of laminae and articular processes, and accuracy. Conclusion: Intraoperative ultrasound can be used for spine surgery neuronavigation. We demonstrated that the IGNS system yield acceptable accuracy and high efficiency compared to the standard CT-based navigation procedure. The flexibility of the iUS acquisitions can have repercussions on the system performance, which are not fully identified. Further investigation is needed to understand the relationship between iUS acquisition and alignment performance.